Role of Defensins in Corneal Epithelial Barrier Function against Pseudomonas aeruginosa Traversal - Augustin, Danielle K. (American Society for Microbiology (ASM), 2011)
Studies have shown that epithelium-expressed antimicrobial peptides (AMPs), e.g., β-defensins, play a role in clearing bacteria from mouse corneas already infected with Pseudomonas aeruginosa. Less is known about the role of AMPs in allowing the cornea to resist infection when healthy. We previously reported that contact lens exposure, a major cause of P. aeruginosa keratitis, can inhibit the upregulation of human β-defensin 2 (hBD-2) by corneal epithelial cells in response to P. aeruginosa antigens in vitro. Here, we studied the role of AMPs in maintaining the corneal epithelial barrier to P. aeruginosa penetration using both in vitro (human) and in vivo (mouse) experiments. Results showed that preexposing human corneal epithelial multilayers to bacterial antigens in a culture supernatant (known to upregulate AMP expression) reduced epithelial susceptibility to P. aeruginosa traversal up to 6-fold (P < 0.001). Accordingly, small interfering RNA (siRNA) knockdown of any one of four AMPs expressed by human epithelia promoted P. aeruginosa traversal by more than 3-fold (P < 0.001). The combination knockdown of AMPs further enhanced susceptibility to bacterial traversal by ∼8-fold (P < 0.001). In vivo experiments showed that the loss of murine β-defensin 3 (mBD-3), a murine ortholog of hBD-2, enhanced corneal susceptibility to P. aeruginosa. The uninjured ocular surface of mBD-3(−/−) mice showed a reduced capacity to clear P. aeruginosa, and their corneal epithelia were more susceptible to bacterial colonization, even when inoculated ex vivo to exclude tear fluid effects. Together, these in vitro and in vivo data show functional roles for AMPs in normal corneal epithelial cell barrier function against P. aeruginosa.